Chasing the water: the political economy of water management and catchment development in the Karamoja-Turkana Complex (KTC), Uganda - Nicol, Alan; Debevec, Liza; Okene, S. (International Water Management Institute, 2021)
The history of Karamoja, a subregion in the far northeast of Uganda, is complex and scarred by conflict. For centuries, this subregion has been a remote area of agropastoralism situated on the sociological and ecological border between the Nile and Turkana basins. At the far eastern tip of the Nile Basin, a sweeping escarpment from Karamoja runs down into the Lake Turkana Basin with major temperature and rainfall gradients that result in significant patterns of transhumance, as the Turkana people to the east seek access to the more plentiful water and grazing resources in Karamoja to the west. In this paper, we call this complex of relations and resources the ‘Karamoja-Turkana Complex’ (KTC) and examine the political-economy relationships therein. We look at policy on water resources management and development, including choices made on siting and developing water sources, the kinds of narratives employed by the government, and the underlying tensions and conflicts between major social groups sharing these scarce resources. We base our analysis of the situation on a wider assessment of the water management challenges combined with a detailed examination of two large dams – Arachek and Longoromit – recently constructed in the Karamoja subregion. Findings from the study highlighted that (i) interlinked systems within the KTC can generate new disputes and pressures on resources; (ii) water management within Karamoja and Turkana requires a broader view that extends beyond the watershed, because competition for water is part of the wider context of KTC; and (iii) power structures and processes associated with the development of water structures are important but poorly understood despite continued resource allocation. The paper makes four recommendations: (i) catchment management institutions need to take ownership of new developments; (ii) a checklist is provided to achieve more effective outcomes from the siting and design of surface water storage structures; (iii) improve management oversight after completion of projects; and (iv) undertake water-pasture management consultations across the KTC.